Mothers’ Empowernment In Weaning Food Serving For Toddler Nutrition Needs At Mario Village, Mare Subdistrict Bone Regency - Ismawati; Sulfianti; Indryani (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Mario Village, Mare Subdistrict, is one of the priority villages for stunting prevention and reduction in Bone Regency in 2021. Mario Village, Mare Subdistrict, is the 6th (six) of 50 (fifty) priority villages for stunting prevention and reduction in 2021. To achieve this goal, it is necessary for cross-sectoral collaboration in fulfilling optimal community nutrition, especially nutrition for children under five/toddler. Toddler nutrition is very important to have special attention due to economic limitations and lack of knowledge in fulfilling optimal nutrition, especially in the serving of appropriate weaning food (MP-ASI). Lecturers are present in their efforts to provide solutions so that optimal nutrition can be fulfilled by giving counseling methods such as: (1) Nutritional status of toddlers and the impact and dangers of poor nutritional status (2) Appropriate weaning food based on age (3) Appropriate, correct and adequate weaning food (4) Demonstration of weaning food (MPASI) broth serving by using a participatory method.